Penetrating Facial Trauma Resulting in Loss of Sense - Petrus, Asan; Zansen, Jakaria (SCRIPTA SCORE Scientific Medical Journal, 2023)
Introduction. Clinical forensic medicine interacts between the law, the judiciary and the police involving living and dead people with the issuance of a visum et repertum. A wound is damage to a part of the body in the form of a break in the integrity of the tissue that can occur due to mechanical violence. The eye organ is particularly vulnerable to injury, which can be fatal and lead to blindness. Trauma is the leading cause of unilateral blindness. Approximately 3 million cases of ocular and orbital trauma occur in the United States each year. An estimated 20,000 to 68,000 of these cases are visually impairing and approximately 40,000 have significant vision loss. Objective. To review forensic and medicolegal cases of sharp facial trauma to sensory loss. Case Illustration. Reported a case of stabbing a woman who was riding a motorcycle with the intention of the perpetrator to seize the victim's motorcycle. Discussion. the results of the examination, the victim is a woman, 54 years old, the patient's general condition is good, cooperative compos mentis consciousness, and examination of vital signs within normal limits. On examination, there were stab wounds on the face covering the forehead, nose and right cheek to the right eyeball due to sharp trauma. It was confirmed that the condition of the victim's left eye was categorized as blind, the eye could not see anymore because the eyeball had been cut and bleeding occurred so that the removal of the eyeball organ had to be done to avoid complications from the injury, but in this case the victim refused to take this action. Conclusion. Based on this injury, the victim suffered a loss of vision. This case constitutes serious injury pursuant to Article 90 of the Penal Code and the suspect is charged under Article 355 of the Penal Code. Key Point: Forensic and Medicolegal, Loss of Sense, Penetrating Facial Trauma